Point-of-Care Hemoglobin Testing for Early Anemia Detection in Adolescent Girls: A Qualitative Study in Indonesia - Maryam; Endang Susilowati (HM Publisher, 2025)
Anemia is a significant public health issue, particularly among adolescent girls in developing countries like Indonesia. Early detection and management are crucial for preventing adverse health outcomes. Point-of-care testing (POCT) for hemoglobin levels offers a promising approach for anemia screening in resource-constrained settings. This study aimed to explore the feasibility and acceptability of POCT for anemia detection among adolescent girls in an Indonesian school setting. A qualitative study was conducted at an Islamic boarding school (Madrasah) in Indonesia. Participants included adolescent girls aged 12-18 years. Data were collected through semi-structured interviews with students, teachers, and healthcare providers. Additionally, focus group discussions were held with students to gather diverse perspectives on anemia and POCT. Thematic analysis was used to analyze the transcribed data. The findings revealed a high prevalence of anemia among the participants. Menstrual blood loss, dietary habits, and lack of awareness about anemia were identified as contributing factors. POCT was perceived as convenient and accessible, with most participants expressing a positive attitude towards its use for anemia screening. However, some concerns were raised regarding the accuracy of the test and the need for trained personnel to interpret the results. In conclusion, POCT for hemoglobin holds the potential for early anemia detection in adolescent girls. The integration of POCT into school health programs can facilitate timely interventions and improve anemia management. Further research is needed to evaluate the effectiveness of POCT-based screening programs and their impact on anemia prevalence in this population.